2020
DOI: 10.1161/circulationaha.119.044183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dapagliflozin on Atrial Fibrillation in Patients With Type 2 Diabetes Mellitus

Abstract: Background: Atrial fibrillation (AF) and atrial flutter (AFL) are associated with both diabetes mellitus and its related comorbidities, including hypertension, obesity, and heart failure (HF). SGLT2 (sodium-glucose cotransporter 2) inhibitors have been shown to lower blood pressure, reduce weight, have salutary effects on left ventricular remodeling, and reduce hospitalization for HF and cardiovascular death in patients with type 2 diabetes mellitus. We therefore investigated whether SGLT2 inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
180
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 299 publications
(213 citation statements)
references
References 33 publications
12
180
0
3
Order By: Relevance
“…The main mechanisms of their cardioprotective effects are improvements in cardiac cell metabolism and ventricular loading conditions, inhibition of Na + /H + exchange in myocardial cells, alterations in adipokine and cytokine production, and reductions in cardiac cell necrosis and cardiac fibrosis [ 34 , 35 ]. SGLT2i has also been shown to reduce sympathetic overdrive, which plays an important role in the development of AF [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main mechanisms of their cardioprotective effects are improvements in cardiac cell metabolism and ventricular loading conditions, inhibition of Na + /H + exchange in myocardial cells, alterations in adipokine and cytokine production, and reductions in cardiac cell necrosis and cardiac fibrosis [ 34 , 35 ]. SGLT2i has also been shown to reduce sympathetic overdrive, which plays an important role in the development of AF [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CVD-REAL Nordic study also indicated that dapagliflozin was associated with lower risks of cardiovascular events and all-cause mortality but a neutral risk of AF (HR: 0.92; [95% CI 0.76–1.12]; P = 0.414) compared with DPP-4is in a real-world clinical setting [ 19 , 20 ]. Conversely, post-hoc analysis of the DECLARE-TIMI 58 trial indicated that dapagliflozin reduced the risk of AF/AFL by 19% (HR: 0.81; [95% CI 0.68–0.95]; P = 0.009) and the number of total AF/AFL events by 23% compared to placebo in 17,160 T2DM patients, regardless of the presence or absence of AF/AFL, established cardiovascular disease, or heart failure at baseline [ 18 ]. To the best of our knowledge, only the CVD‐REAL Nordic study has directly compared the risk of AF between SGLT2i and DPP4i treatment among T2DM patients in a real-world setting [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20] SGLT2i has also been shown to reduce sympathetic overdrive, which plays an important role in the development of AF. [21] Other diabetes medications including metformin, thiazolidinedione (TZD), and DPP4i, may also be associated with a lower risk of AF. A previous study of a nationwide, population-based dynamic cohort indicated that the use of metformin was associated with a decreased risk of AF in T2DM patients who were not using other antidiabetic drugs, probably by attenuating atrial cell tachycardia-induced myolysis and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the post-hoc analysis of the DECLARE-TIMI 58 trial indicated that dapagli ozin signi cantly reduced the risk of AF/atrial utter (AFL) in T2DM patients. [18] However, the CVD-REAL Nordic showed no signi cant difference of the new-onset AF associated with the use of dapagli ozin compared with dipeptidyl peptidase-4 inhibitor (DPP4i) or other glucose-lowering agents in T2DM patients in real-world practice. [19,20] Therefore, the primary aim of the present study was to investigate whether SGLT2i is associated with a decreased risk of incident AF compared with DPP4i, speci cally focused on Asian population with T2DM, in a large real-world setting.…”
Section: Introductionmentioning
confidence: 98%